Antibacterial Activity of Venom from the Puff Adder (Bitis arietans), Egyptian Cobra (Naja haje), and Red Spitting Cobra (Naja pallida) - Okumu, Mitchel Otieno; Eyaan, Kennedy Lojau; Bett, Luke Kipkorir; Gitahi, Nduhiu (International Journal of Microbiology, 2023)
Bitis arietans (Puff adder), Naja haje (Egyptian cobra), and Naja pallida (Red spitting cobra) venoms were tested for antimicrobial activity. This evaluation employed disc diffusion and microbroth dilution techniques. Gram-positive bacteria (Bacillus cereus and Staphylococcus aureus) and Gram-negative bacteria (Escherichia coli, Klebsiella pneumonia, and Salmonella typhi) were used. Aztreonam (30 µg), cefpodoxime (10 µg), cefoxitine (30 µg), streptomycin (25 µg), ceftriaxone (30 µg), nalidixic acid (30 µg), tetracycline (30 µg), and sulfamethoxazole (25 µg) were used as controls. All tests were conducted in triplicate (n = 3). Results. The activity of B. arietans venom against Gram-negative bacteria was significantly lower (p<0.001) than that of controls. The efficacy of B. arietans venom and sulfamethoxazole against both Gram-positive and Gram-negative bacteria was not significantly different (p>0.9999). The efficacy of B. arietans venom against Gram-positive bacteria was significantly lower (p<0.001) than cefoxitin, streptomycin, and tetracycline. The efficacy of N. haje venom against Gram-negative bacteria was significantly lower (p<0.001) than that of controls. There was no significant difference in the antimicrobial efficacy of N. haje venom and controls against Gram-positive bacteria (p=0.3927 to p=0.9998). There was no significant difference in the efficacy of N. pallida venom and controls against Gram-negative bacteria (p=0.3061 to p=0.9981). There was no significant difference in the efficacy of N. pallida venom and controls against Gram-positive bacteria (p=0.2368 to p>0.9999). Conclusions. Of all the tested venoms, only Naja pallida venom showed good efficacy against both Gram-positive and Gram-negative bacteria.